Anticolonial co-design: a methodology for including agricultural workers in the development of new AgTech - Mira O’Connor; Karly Ann Burch; Sandhiya Gounder (Kōtuitui, 2025)
Collaborative design (co-design) is becoming a popular method for including end-users in the design process of technologies which may affect them. The research in this paper emerges from an agricultural technology (AgTech) co-design project located in settler colonial state of Aotearoa New Zealand. Inspired by methodological insights from anticolonial science and technology studies (STS), the paper details the authors’ experiences with attempting to include local and migrant agricultural workers within the AgTech co-design project in a way that did not perpetuate colonialism (i.e. was anticolonial). Based on these experiences, the authors identify four practices that can support other researchers wanting to engage in anticolonial co-design: (1) understand the historical context of your research; (2) create a place –and community-based guidelines for technology development; (3) build and maintain strong relationships with collaborators; and (4) be prepared to slow-down or to stop innovation. These practices offer methodological insights into how to do anticolonial co-design within the uneven power relations of settler colonialism and within projects not necessarily designed to engage in anticolonial co-design.